Management of vulvar Behçet's disease: case report - Méndez Vega, Diana Alejandra (2023)
Behçet's disease (BD) is an inflammatory, multisystemic, relapsing-remitting disorderof unknown etiology. A key feature of the disease is orogenital ulceration that causesconsiderable morbidity with great impact on patient’s quality of life. Its medicalmanagement consists of a scheme with colchicine, steroids or immunomodulators.We report the case of a patient with genital lesions who consulted on multipleoccasions, receiving antibiotics and even surgical management, with refractoryresponse to these interventions. Subsequently, due to the characteristics of the lesionand clinical behavior, Behçet's disease was suspected and medical managementwith oral steroids and cures with phytostimulin was initiated. The genital ulcers wereresolved, and the patient was subsequently taken to surgery for correction of thevulvar synechiae.